Pengaruh Motivasi Kerja, Manajemen Pengetahuan dan Dukungan Organisasi Terhadap Kinerja Karyawan Hotel Chanti Semarang - Lusy Diah; Krisnawati Setyaningrum Nugraheni (Politeknik Pariwisata NHI Bandung, 2021)
This study aims to analyze the effect of work motivation, knowledge management and organizational support on employee performance at Hotel Chanti Semarang. This research uses quantitative descriptive which describes factual conditions with data collected from questionnaires based on direct observation of objects and interviews. Population and sample in this study were 64 employees of Hotel Chanti Semarang. Descriptive analysis through frequency and percentage, as well as statistical analysis using Multiple Linear Regression. The findings of this study, namely Work Motivation, Knowledge Management, and Organizational Support have been applied by employees and have had a positive and significant influence both simultaneously and partially on the performance of employees of Hotel Chanti Semarang. The results of the analysis show that all observed variables in the form of Work Motivation, Knowledge Management and Organizational Support are significant based on the acquisition of tcount > ttable, and it is found that the dominant influence of Organizational Support (X3) affects the Employee Performance of Chanti Hotel Semarang